2018
DOI: 10.1002/wrna.1520
|View full text |Cite
|
Sign up to set email alerts
|

Diverse roles of RNA‐binding proteins in cancer traits and their implications in gastrointestinal cancers

Abstract: Gene expression patterns in cancer cells are strongly influenced by posttranscriptional mechanisms. RNA-binding proteins (RBPs) play key roles in posttranscriptional gene regulation; they can interact with target mRNAs in a sequence-and structure-dependent manner, and determine cellular behavior by manipulating the processing of these mRNAs. Numerous RBPs are aberrantly deregulated in many human cancers and hence, affect the functioning of mRNAs that encode proteins, implicated in carcinogenesis. Here, we summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 231 publications
(363 reference statements)
1
70
0
Order By: Relevance
“…RNA binding proteins (RBPs) are proteins that interact with various types of RNA and are ubiquitously expressed in cells (Masuda and Kuwano, 2019;New et al, 2019;Otsuka et al, 2019). A total of 1542 RBPs have been identified by highthroughput screening in human cells, representing 7.5% of all protein coding genes (Gerstberger et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA binding proteins (RBPs) are proteins that interact with various types of RNA and are ubiquitously expressed in cells (Masuda and Kuwano, 2019;New et al, 2019;Otsuka et al, 2019). A total of 1542 RBPs have been identified by highthroughput screening in human cells, representing 7.5% of all protein coding genes (Gerstberger et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1542 RBPs have been identified by highthroughput screening in human cells, representing 7.5% of all protein coding genes (Gerstberger et al, 2014). These RBPs affect post-transcriptional events in cells and modulate cell physiology, and are therefore involved in multiple biological processes including RNA splicing, mRNA stability, export to the cytoplasm, localization, and protein translation (Masuda and Kuwano, 2019;Nahalka, 2019). Given that RPBs perform various critical functions in post-transcriptional events, it is unsurprising that alterations in RBPs are closely related to the initiation and progression of many human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, it mostly behaves as a tumor suppressor in acute leukemia [12]. RBPs constitute a key factor of the post-transcriptional process and play an important role in the regulation of RNA in gastrointestinal [13] and colorectal cancers [14]. Despite the emergence of RBPs as key regulators of every cancer hallmark, very little is known about their potential mechanisms and downstream carcinogenic targets, particularly with regard to bladder cancer.…”
mentioning
confidence: 99%
“…Liver cancer is influenced by post-transcriptional mechanisms that dynamically regulate protein expression. (Wong et al 2018;Goldstrohm et al 2018) Cis-regulatory RNA elements and trans-acting factors (Gerstberger et al 2014;Moore 2005) including RNA-binding proteins (RBPs) play an essential role in gene expression in cancer cells (Masuda & Kuwano 2019). Recently, a group of RBPS termed MEX-3 RNA binding family member (MEX3) was identified in the nematode Caenorhabditis elegans (Ciosk et al 2006) and revealed one of the few RBPs with carcinogenic or tumor suppressor activity (Kim et al 2009;Pereira et al 2013a).…”
Section: Introductionmentioning
confidence: 99%